THE INVESTIGATING METAPHORS OF TEACHERS ABOUT CONCEPT OF DIGITAL LITERACY - Elif GÜVEN DEMİR (Fırat University, 2019)
The purpose of the study is examining the metaphors towards digital literacy of primary school and secondary school teachers. Learning features, methods and expectations from learners has changed with the developing technology. Generation called digital natives use technology indefeasibly who prefer technology based educational processes. Changing society expectations affect the learner profile and features. Requirements of new century and potentials of i